POTENSI FAMILI ASTERACEAE SEBAGAI OBAT TRADISIONAL DI MASYARAKAT ETNIS SIMALUNGUN KABUPATEN SIMALUNGUN PROVINSI SUMATERA UTARA - Simanjuntak, Helena Anjelina (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2017)
Simalungun is one of the regencies in North Sumatera province that has various ethnic one of them is Simalungun ethnic. The ethnic community simalungun still use natural materials such as plants in the treatment of various diseases. From the research that has been done found some types of plants that have potential as a traditional medicine that is dominated by the types of Asteraceae family. There are 10 species of Asteraceae family that have potential as traditional medicine: Achillea santolina, Ageratum conyzoides, Cosmos caudatus, Eclipta alba, Emilia sonchifolia, Eupatorium riparium, Gynura segetum, Sonchus arvensis, Tithonia diversifolia, and Wedelia calendulaceae. Potential drugs such as Abdominal pain medication, Drug Injury, Appetite Enhancer, Hair Fertilizer, Peluruh Air Art, Hypertension, and Kidney Stone. Plant part used is part of Leaf.